Perception disorders and behavior changes in high-altitude mountaineers - Banasiewicz, Tomasz; Przybył, Magdalena; Holdys, Joanna (Akademia Wychowania Fizycznego w Poznaniu)
High-altitude mountaineering involves exposure to reduced partial oxygen pressure, which leads to a number of psychical and physical disturbances in the climber’s body and has an impact on the function of the central nervous system. These disorders can be intensified by external environmental factors such as energy deficit, fatigue, high true altitude, stress and cold. The climber’s central nervous system can experience functional and morphological changes, mostly of a non-permanent character. All these factors can lead to perception disorders and changes of behavior in climbers as compared with their perception abilities and behaviors at lower altitudes. Problems with concentration, rational assessment of situations and one’s own capabilities –and in extreme cases – delusions or autistic symptoms may also occur. Emphatic behaviors of climbers at high altitudes seem to be seriously hindered, since their brain function focuses on survival. An assessment of ethical behaviors in such conditions is very difficult as humans normally behave ethically at “sea-level” where the brain functions properly in under appropriate partial oxygen pressure
Keywords: high altitude sickness; behavior changes; hypoxia; alpine conditions; climbing; perception disorders